3D thermal analysis of rectangular microscale inorganic light-emitting diodes in a pulsed operation. (9th September 2016) - Cui, Y; Bian, Z; Li, Y; Xing, Y; Song, J
Abstract: Microscale inorganic light-emitting diodes ( µ -ILEDs) have attracted much attention due to their excellent performance in biointegrated applications such as optogenetics. The thermal behaviors of µ -ILEDs are critically important since a certain temperature increase may degrade the LED performance and cause tissue lesion. The µ -ILEDs in a pulsed operation offer an advantage in thermal management. In this paper, a 3D analytic model, as validated by finite element analysis, is developed to study the thermal response of rectangular µ -ILEDs in a pulsed operation. A scaling law for the maximum normalized temperature increase of rectangular µ -ILEDs in terms of non-dimensional parameters is established. The influences of geometric (i.e. shape factor) and loading parameters (e.g. duty cycle and period) on the temperature increase are systematically investigated. These results are very helpful in designing µ -ILEDs by providing guidelines to avoid adverse thermal effects.